2016
DOI: 10.1007/s00894-015-2904-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes of a sodium dodecyl sulfate (SDS) micelle induced by alcohol molecules

Abstract: Coarse-grained dynamical simulations have been performed to investigate the behavior of a surfactant micelle in the presence of six different alcohols: hexanol, octanol, decanol, dodecanol, tetradecanol, and hexadecanol. The self-assembly of sodium dodecyl sulfate (SDS) is modified by the alcohol molecules into cylindrical and bilayer micelles as a function of the alcohol/SDS mass ratio. Therefore, in order to understand, from a molecular point of view, how SDS and alcohol molecules self-organize to form the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…The SANS data for the d 25 -SDS system is modelled instead to show the presence of corpuscular/oblate ellipsoidal aggregates which we take to be mixed SDS/co-surfactant bicelles, with around 30% SDS and 70% cetyl/stearyl alcohol. There have been no other reports of aggregates of this type being seen in aqueous creams but it is pertinent here to note that Zarbahksh et al have repeatedly observed surfactant-rich layers which they speculate to contain surfactant micelles in the aqueous phase close to the surfactant monolayers formed at the decane-and hexadecane-water interfaces 22,39,40 , and Méndez-Bermúdez and Dominguez have shown through coarse grain molecular dynamics simulations that bilayer aggregates of this type are formed in aqueous dispersions of SDS and hexadecanol when the proportion of hexadecanol is high 41 . Experimentally, when the component oil and aqueous phases are mixed in the preparation of a cream, such aggregates would likely serve as intermediaries in the transfer of amphiphiles between the lamellae and the surfaces of the oil droplets.…”
Section: Discussionmentioning
confidence: 84%
“…The SANS data for the d 25 -SDS system is modelled instead to show the presence of corpuscular/oblate ellipsoidal aggregates which we take to be mixed SDS/co-surfactant bicelles, with around 30% SDS and 70% cetyl/stearyl alcohol. There have been no other reports of aggregates of this type being seen in aqueous creams but it is pertinent here to note that Zarbahksh et al have repeatedly observed surfactant-rich layers which they speculate to contain surfactant micelles in the aqueous phase close to the surfactant monolayers formed at the decane-and hexadecane-water interfaces 22,39,40 , and Méndez-Bermúdez and Dominguez have shown through coarse grain molecular dynamics simulations that bilayer aggregates of this type are formed in aqueous dispersions of SDS and hexadecanol when the proportion of hexadecanol is high 41 . Experimentally, when the component oil and aqueous phases are mixed in the preparation of a cream, such aggregates would likely serve as intermediaries in the transfer of amphiphiles between the lamellae and the surfaces of the oil droplets.…”
Section: Discussionmentioning
confidence: 84%
“…As an important component in chemical flooding, understanding the roles of cosurfactants is of great significance. Many studies have been carried out to clarify their roles at water–air or water–oil interfaces, such as theories, experiments, and simulations ,, (Table ). The most commonly used cosurfactants in chemical flooding are medium-chain alcohols, including propyl, butyl, and pentyl alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…to determine the effect of methanol, ethanol, n-propanol and iso-propanol on SDS/water systems [18][19][20] . Research on other SDS/alcohol/water systems has been reported by several authors [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Volumetric Measurements Have Been Madementioning
confidence: 99%
“…Among many the structure of SDS micelles in water has been characterized by various methods, e.g. have been chosen for this study 18 .…”
Section: Introductionmentioning
confidence: 99%